Evaluative skill in the creative process: A cross-cultural study. (March 2023) - Guo, Yawei; Lin, Shengjie; Williams, Zachary J.; Zeng, Yuntao; Cole Clark, Lili Q.
Highlights: Measurement invariance of two evaluative measures was examined cross-culturally. A two-factor model was supported in both the American and Chinese groups. The model satisfied configural, weak and partial strong invariance cross-culturally. Latent mean comparisons suggested higher evaluative skill of Americans on Uses task. Abstract: Evaluative skill is the ability to accurately judge ideas on creativity (or originality), which is a critical component of creativity. Various aspects of creativity have been examined cross-culturally, but little research has focused on evaluative skill. The first goal of this study was to examine the measurement invariance of evaluative skill assessments, which were based on two types of divergent thinking tests (Line Meanings and Uses), between American ( n = 341) and Chinese ( n = 345) college students. Multi-group confirmatory factor analyses supported a two-factor model based on two types of evaluation tasks, and this model satisfied configural and weak invariance. However, partial strong invariance was satisfied only for the Uses evaluation task. Based on this evidence, our second goal was to explore the differences in evaluative skill between these two groups. Via latent mean comparisons, we found that American participants had better performance on evaluative skill based on the Uses evaluation task than their Chinese counterparts. Taken together, this study is one of the first to examine the cross-cultural differences in evaluative skill between American and Chinese adults. This study offered preliminary results showing some invariance in evaluative skill assessments across cultures and indicating cross-cultural differences in this ability.